358. Comparison of Voriconazole (VORI), Isavuconazole (ISAV), and Posaconazole (POSA) in the Initial Treatment of Patients With Invasive Aspergillosis (IA). (26th November 2018) - Cheng, Matthew P; Orejas, José Luis; Arbona-Haddad, Esther; Marty, Francisco M; Koo, Sophia; Hammond, Sarah
Abstract: Background: While VORI is recommend as first-line therapy for patients with IA, ISAV, and POSA have been approved for the treatment and prophylaxis of IA, respectively. We evaluated treatment responses among patients with IA receiving triazole antifungals. Methods: We performed a retrospective cohort study at our center in patients diagnosed with probable or proven IA between March 2015 and January 2018 who were initially treated with VORI, ISAV, or POSA. Patients were followed until April 2018. Baseline characteristics, laboratory parameters, and clinical evolution were documented. We captured changes in antifungal therapy due to lack of drug efficacy (clinical, radiographic, or mycological progression) and changes in response to drug toxicities. Results: A total of 73 patients were diagnosed with IA (55 probable, 18 proven) during the study period. Median age was 61 years (range, 19–80) and 37 (50.7%) were male. At IA diagnosis, 57 (78.1%) had an active hematological malignancy, 27 (37%) had undergone hematopoietic-cell transplantation, and 10 (13.7%) had undergone solid organ transplantation. Sixty-two patients (84.9%) were neutropenic, 42 (57.5%) were on glucocorticoids > 0.3 mg/kg/day prednisone-equivalents in the 3 weeks preceding diagnosis, and 43 (58.9%) were on other T-cell immunosuppressants. Thirty-six patients were initially treated with VORI for a median of 20 days (range, 1–453), 29 with ISAV for a median of 35 days (range, 1–714), and 8 with POSA for a median of 15 days (range, 2–399). Pulmonary-only IA was treated initially with POSA in 87.5%, VORI in 86.1% and ISAV in 65.5% of patients. ISAV was more commonly used in patients with extrapulmonary involvement (44.5%) compared with VORI (13.9%) or POSA (12.5%). Antifungal changes due to lack of efficacy or drug toxicities were: 2.8% and 22.2% for VORI, 24.1% and 3.4% for ISAV, and 37.5% and 25.0% for POSA. In an analysis based on initial treatment not accounting for later changes, the EORTC/MSG clinical success rate at 6 weeks was 33.3%, 31.0%, and 12.5% for VORI, ISAV, and POSA, respectively. Conclusion: While the drug efficacy and toxicity rates varied among agents, the 42-day clinical success rate did not. Further research is warranted to determine the optimal antifungal agent for patients with IA. Disclosures: F. M. Marty, Merck: Consultant and Investigator, Consulting fee, Research support and Speaker honorarium. Astellas: Consultant and Investigator, Consulting fee and Research support. Chimerix: Consultant and Investigator, Consulting fee and Research support. Fate Therapeutics: Consultant, Consulting fee. GlaxoSmithKline: Consultant, Consulting fee. LFB: Consultant, Consulting fee. Roche Molecular Diagnostics: Consultant, Consulting fee. Shire: Consultant and Investigator, Consulting fee and Research support. S. Hammond, Merck: Investigator, Research support.